The development of control scheme for single phase induction motor - Sumi Murni, Zakaria (2010)
The purpose of this study is in electronic scope to develop a control scheme for single phase induction motor application. This project is focus on the AC motor speed control by varying the duty cycle of Pulse Width Modulation (PWM) signal. PWM speed control is desirable due to its high power efficiency compare with another method of speed control like frequency control, current and voltage control. The use of the control systems can add speed variation to the systems. Control schemes should be determined based on the control necessary, the cost and the process. The driver circuit will boosted the PWM signal to drive the MOSFET and thus control the motor. The speed of AC motor is depending on the spectrum of PWM that refer to their duty cycle. This project was able to control the motor speed.